2017
DOI: 10.1017/cjn.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

A System-Based Intervention to Improve Access to Hyperacute Stroke Care

Abstract: Background: Hyperacute stroke is a time-sensitive emergency for which outcomes improve with faster treatment. When stroke systems are accessed via emergency medical services (EMS), patients are routed to hyperacute stroke centres and are treated faster. But over a third of patients with strokes do not come to the hospital by EMS, and may inadvertently arrive at centres that do not provide acute stroke services. We developed and studied the impact of protocols to quickly identify and move "walk-in" patients fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Research in several countries including the US, Canada, the Netherlands, Denmark, and Australia suggests that this approach may improve provision of evidence based care processes for all stroke patients, by increasing access to specialist care and thrombolysis where appropriate 910 11 12 13 14 Although improved clinical outcomes among patients admitted to organised inpatient stroke care are well documented, relatively little evidence exists to show whether centralising acute stroke care to a small number of high volume specialist centres produces better clinical outcomes at the system level across all stroke patients 1516 Our previous research showed reductions in mortality after the centralisation of stroke services in London (see below).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in several countries including the US, Canada, the Netherlands, Denmark, and Australia suggests that this approach may improve provision of evidence based care processes for all stroke patients, by increasing access to specialist care and thrombolysis where appropriate 910 11 12 13 14 Although improved clinical outcomes among patients admitted to organised inpatient stroke care are well documented, relatively little evidence exists to show whether centralising acute stroke care to a small number of high volume specialist centres produces better clinical outcomes at the system level across all stroke patients 1516 Our previous research showed reductions in mortality after the centralisation of stroke services in London (see below).…”
Section: Introductionmentioning
confidence: 99%
“…Ethical approval: The study received ethical approval in September 2011 from the London East NHS Research Ethics Committee (ref 11/LO/1396).…”
mentioning
confidence: 99%
“…Houve eficiência da pré-notificação hospitalar (Kendall;Dutta;Brown, 2015), maio acesso a centros de AVC (Hsieh et al, 2016) e redução da mortalidade (Hsieh et al, 2016;Kodankandath et al, 2017). Houve aumento da taxa da população a 30 minutos de um centro de AVC (Swartz et al, 2017), redução de internações em centros que costumam ter uma carga excessiva de trabalho (Tan et al, 2017), mantendo os pacientes mais próximos de casa (Jewett et al, 2017) e melhorando a qualidade de vida dos que vivem em área rural (Klingner et al, 2018). Potencialização da colaboração entre níveis de saúde e entre profissionais (Jewett et al, 2017;Kodankandath et al, 2017) e favorecimento da integração de capital humano, tecnologia e procedimentos, universalizando os cuidados de saúde (Kodankandath et al, 2017).…”
Section: Telemedicinaunclassified
“…In several countries, acute stroke services are being centralized into "hub and spoke" systems in which hospital providing different levels of care work together to create a centralized system in which all patients with acute ischemic stroke are taken to specialized centers, rather than the nearest hospital [60]. Research suggests that in countries where such models exist (e.g., the United States, Canada, the Netherlands, Denmark, and Australia), there is greater provision of evidence-based therapies by increasing access to specialist care and thrombolysis [61][62][63]. Other countries, such as the United Kingdom, have found decreases in mortality and hospital length-of-stay where hyperacute stroke services were centralized to a small number of highly specialized, highvolume centers [64].…”
Section: Cerebrovascular Diseasementioning
confidence: 99%